The Rockefeller University Clinical Scholars (KL2) program 2006–2016. Issue 5 (2nd February 2018) - Schlesinger, Sarah J.; Romanick, Michelle; Tobin, Jonathan N.; Brassil, Donna; Kost, Rhonda G.; Devine, Rita; O'Sullivan, Barbara; Vaughan, Roger D.; Liang, Yupu; Correa da Rosa, Joel; Williams, Maija; Krueger, James G.; et al.
Abstract : Introduction and Methods: The Rockefeller Clinical Scholars (KL2) program began in 1976 and transitioned into a 3-year Master's degree program in 2006 when Rockefeller joined the National Institute of Health Clinical and Translational Science Award program. The program consists of ∼15 trainees supported by the Clinical and Translational Science Award KL2 award and University funds. It is designed to provide an optimal environment for junior translational investigators to develop team science and leadership skills by designing and performing a human subjects protocol under the supervision of a distinguished senior investigator mentor and a team of content expert educators. This is complemented by a tutorial focused on important translational skills. Results: Since 2006, 40 Clinical Scholars have graduated from the programs and gone on to careers in academia (72%), government service (5%), industry (15%), and private medical practice (3%); 2 (5%) remain in training programs; 39/40 remain in translational research careers with 23 National Institute of Health awards totaling 23 million, foundation and philanthropic support of 20.3 million, and foreign government and foundation support of 6 million. They have made wide ranging scientific discoveries and have endeavored to translate those discoveries into improved human health. Conclusion: The Rockefeller Clinical Scholars (KL2) program provides one model for translational science training.